2010
DOI: 10.4028/www.scientific.net/msf.660-661.1130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of S/S Process of Tannery Waste in Cement by Structural and Mechanical Analysis

Abstract: This paper presents a study of a stabilization/solidification (S/S) process of a tannery waste containing chromium. In this process a mixture of cement, water and the waste is solidified during hydration of the former. Stabilization occurs by the reaction of the chromium components of the waste with the calcium hydroxide formed during the process. A rigid block is obtained with low hazardous of contamination of soil and groundwater after its disposal into industrial landfill. Mixtures were prepared adding drie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…According to the results obtained by the authors, the addition of potassium dichromate promoted significant reductions in resistance values, attributed to inhibition and delay of cement hydration. Pinto et al, [29] in their study on stabilization by solidification of tannery residue, also observed that the increase in the were also verified by por Costa et al, [31] and according to the authors, this behavior refers to the conversion of dichromate ions into chromate ions, influenced by the pH change of the solution promoted by the addition of cement. For the construction of the analytical curve, the absorbance values of the verified solutions for the wavelength of 372 nm were considered.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…According to the results obtained by the authors, the addition of potassium dichromate promoted significant reductions in resistance values, attributed to inhibition and delay of cement hydration. Pinto et al, [29] in their study on stabilization by solidification of tannery residue, also observed that the increase in the were also verified by por Costa et al, [31] and according to the authors, this behavior refers to the conversion of dichromate ions into chromate ions, influenced by the pH change of the solution promoted by the addition of cement. For the construction of the analytical curve, the absorbance values of the verified solutions for the wavelength of 372 nm were considered.…”
Section: Resultsmentioning
confidence: 66%
“…As an example of a porosity reducer, bentonite can be cited, which increases in volume when hydrating, obstructing the passage of water through the pores or cracks in the cement matrix [32]. Clays can also be added to the paste to favor the immobilization process, since they can adsorb the metals present in the residues and aid in the mechanical resistance, occupying empty spaces between the hydrated cement components [29]. The association of binders, such as lime and cement, can favor the encapsulation of waste.…”
Section: Resultsmentioning
confidence: 99%
“…As características do resíduo, tais como o seu conteúdo orgânico, conteúdo inorgânico, viscosidade, tamanho e distribuição das partículas podem afetar a qualidade do produto final solidificado. A influência de um mesmo composto dentro da matriz de S/E pode MINOCHA;JAIN;VERMA, 2003;CHEN et al, 2009;PINTO et al, 2010; HEKAL et al, 2011), obtendo como resultado a redução da concentração destes metais e sua capacidade tóxica. Esta técnica deve imobilizar o resíduo perigoso e não alterar as características do cimento(DWECK et al, 2000a).Nos processos de S/E com cimento, o mecanismo de fixação dos metais pesados, em muitas vezes, é através da precipitação química de espécies de baixa solubilidade(CHEN et al, 2009), que está ligada ao pH do sistema.…”
unclassified
“…A formulação contendo rejeito apresentou um aumento de 7% na resistência a compressão em comparação a argamassa controle.No Brasil não há uma legislação específica sobre materiais S/E, para avaliação do processo de S/E das formulações quanto a resistência à compressão, utilizou-se como referência alguns modelos já existentes, que constam na Tabela 4.10, utilizados também por outros autores. Detectou-se que todos os resultados obtidos de resistência à compressão viabilizam a aplicação do processo de S/E sem restrição, valores acima de 0,34 MPa.Em seu trabalho,Pinto et al, (2010) avaliaram o processo de S/E em cimento Portland com adição de resíduo contendo cromo. A presença do resíduo diminuiu a resistência à compressão, efeito oposto foi detectado com adição de aditivos (argilas) nas amostras, comparado a amostra controle.…”
unclassified